Climate change resilience of vulnerable marine species in northwest Europe - Couce, Elena; Pinnegar, John K.; Townhill, Bryony L. (Marine biology, 2025)
Climate change is impacting marine organisms directly through its influence on suitable habitats. We use an ensemble of five ecological niche models to determine how climate change could affect the distribution of species of conservation importance across the northwest European shelf. The models project suitable habitat to the end of the century for 19 sensitive and vulnerable fish and invertebrate species under two climate change scenarios. We found an overall increase in suitable habitat for the species, but with localised decreases and increases at certain localities. Spurdog, thornback and undulate rays and native oyster showed the largest increases in suitable habitat this century, whereas decreases were seen in the slender sea pen, ocean quahog, sea fan and fan mussel. The increases were concentrated in the central and northern North Sea and the decreases to the south and west of the UK, as well as in the southern North Sea. Projected changes in habitat for reef-forming species, means that there could be knock-on impacts to ecosystems and food-webs as species’ distributions shift at different rates. The overall results suggest that most of the mobile species could be relatively robust to climate change in the absence of other human disturbance. However, the results should be considered in the context of human disturbance more broadly. Which future carbon emissions pathway society follows (e.g. RCP4.5 or RCP8.5), will also be a significant determinant as to how much change there will be. The model results described in this study are especially useful in determining which species or areas may benefit from active interventions, to remove barriers to dispersal or provide protection, or from enhanced monitoring and surveillance to inform management.